2017
DOI: 10.18632/oncotarget.23558
|View full text |Cite
|
Sign up to set email alerts
|

Low- to high-density lipoprotein cholesterol ratio followed by coronary computed tomography angiography improves coronary plaque classification accuracy

Abstract: Coronary computed tomography angiography (CCTA) is a noninvasive test for detection and analysis of coronary plaques morphology and classification. The low- to high-density lipoprotein cholesterol (L/H) ratio is associated with plaques vulnerability. The study aims to investigate the diagnostic accuracy of CCTA and L/H ratio for plaques classification. We enrolled 212 patients with coronary artery single-vessel disease who performed preoperative CCTA and Intravascular ultrasound (IVUS)-guided invasive coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…In addition, we also found that LDL-C level and L/H ratio have a good positive correlation with plaque instability. Previous studies pointed out that the L/H ratio is the best pertinent index for predicting the lipid component in coronary plaque and is related to plaque vulnerability, 30,31 which are similar to the results of this study. Combining multiple serological markers may reduce bias in the diagnosis of vulnerable plaque.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we also found that LDL-C level and L/H ratio have a good positive correlation with plaque instability. Previous studies pointed out that the L/H ratio is the best pertinent index for predicting the lipid component in coronary plaque and is related to plaque vulnerability, 30,31 which are similar to the results of this study. Combining multiple serological markers may reduce bias in the diagnosis of vulnerable plaque.…”
Section: Discussionsupporting
confidence: 91%